Development Analysis Religion in Early Age Children in RA DWP UIN Sunan Kalijaga Yogyakarta - Ma'fiyatun Insiyah; Suyadi Suyadi (Fakultas Sains dan Teknologi UIN Sunan Kalijaga, 2017)
This study aims to determine the development of religion into an early childhood in RA DWP UIN Sunan Kalijaga. This research is a qualitative research. Sources of data were obtained from parents and RA DWP teachers UIN Sunan Kalijaga. Data collection is done by the method of observation, interviews and documentation. Data analysis using descriptive qualitative method, namely the presentation of data in written form and explain what it is according to the data obtained from the results of the study. Checking the validity of the data in this study using triagulation techniques and source triagulation. The results of this study indicate that religious development in early childhood is at the level of fairy tales witth religious characteristics as follows: unreflective, egosentric, anthromorphic, verbalited and ritualistic, imitative and wondering.